Stress levels of newborns´ parents in Neonatal Intensive Care Unit - Stübe, Mariléia (2018)
Objective: to evaluate the stress levels of newborns´ parents in the Neonatal Intensive Care Unit. Methods: this is a cross-sectional research with 57 newborn parents. A questionnaire on the sociodemographic data of the newborn and parents and Parental Stress Scale: Neonatal Intensive Care Unit was applied. Frequency analysis, position measurements of the scores, Mann-Whitney test, and Student’s t-test were performed. Results:in the domain “Change in the role of the mother/father”, the concentration of responses was higher in the higher scores; domain“Sounds and images”, in the concentration of responses was higher in the lowest scores, both in the hospitalization and in the discharge of the intensive care unit. Conclusion: parents of infants in the Neonatal Intensive Care Unit presented high levels of stress associated with the “Change in the role of the mother/father” during hospitalization and discharge, and the “Appearance and behavior of the baby” domain at the time of hospitalization.